2016
DOI: 10.1155/2016/6478374
|View full text |Cite
|
Sign up to set email alerts
|

CD63 and GLUT-1 Overexpression Could Predict a Poor Clinical Outcome in GIST: A Study of 54 Cases with Follow-Up

Abstract: Background and Goals. In light of current knowledge, it seems that alternations underlying GISTs are well explained, although all that is enhanced by various aspects on a daily basis. More recently, attention has been pointed towards exosomes as important particles able to modify healthy and also diseased tissues including cancer. The goal of the present study was an analysis of CD9, CD63, and GLUT-1 as a marker of hypoxia status within 54 cases of GIST and evaluation of their predictive value. Methods. 54 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Moreover, CD63 may execute metastasis-promoting functions as a receptor of tissue inhibitor of metalloproteinases interacting with β1 integrins (10). Furthermore, certain studies have revealed that CD63 expression is correlated with a tumor progression and lower survival (3,6,8,(15)(16)(17). Thus, we performed this meta-analysis to better understand the prognostic value of CD63 expression in solid tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, CD63 may execute metastasis-promoting functions as a receptor of tissue inhibitor of metalloproteinases interacting with β1 integrins (10). Furthermore, certain studies have revealed that CD63 expression is correlated with a tumor progression and lower survival (3,6,8,(15)(16)(17). Thus, we performed this meta-analysis to better understand the prognostic value of CD63 expression in solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 5 eligible studies with 1,454 patients for this meta-analysis. Kaprio et al, Miki et al and Lewitowicz at al. reported that positive or high expression of CD63 was associated with poor prognosis in colorectal cancer, gastric cancer and gastrointestinal stromal tumor respectively (3,6,8). On the other hand, Kown et al and Koh et al showed that negative or low expression of CD63 was correlated with a poor survival in lung adenocarcinoma and non-small cell lung cancer respectively (5,7).…”
Section: Discussionmentioning
confidence: 99%
“…In light of Miettinen's classification, Ki-67 could become a promising biomarker. Our experience has taught us to keep a distance from prediction based on MC in cases when just a small biopsy had been taken; thus, we previously tried to focus our attention on other biomarkers [ 26 , 31 – 34 ]. In a very recent paper by Liu et al covering 1022 patients, the cut-off values were stated at 6% which is very close our data, although some methodological differences exist between us [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study has been a natural continuation of our previously published research concerning the significance and the usefulness of GLUT-1, CD9, and CD63 in GIST. The inclusion criteria were previously described in detail [ 26 ]. There was no selection bias.…”
Section: Methodsmentioning
confidence: 99%
“…have reported that urine samples from prostate cancer patients included CD63-positive exosomes[ 7 ]. In addition, CD63 expression has been reported to be a prognostic factor in patients with gastrointestinal stromal tumor[ 8 ]. However, the significance of CD63 in patients with gastric cancer has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%